EPIDEMIOLOGICAL EVALUATION OF HEALTHCARE ASSOCIATED INFECTIONS IN THE CLINIC OF ORAL AND MAXILLO-FACIAL SURGERY "SF.SPIRIDON" EMERGENCY CLINICAL HOSPITAL IASI, ROMANIA - Magda Călina Bârlean; Carina Balcoș; Livia Bobu; Georgiana Macovei; Andra Claudia Gamen; Ionuț Tărăboanță; Cosmin Ionuț Crețu; Ionela-Alina Grosu Creangă; Adina Armencia; Eugenia Popescu (Romanian Society of Oral Rehabilitation, 2020)
The aim of this study was to evaluate epidemiological data on healthcare-associated infections in Oral and Maxillo-Facial Surgery Clinic of the "Sfântul Spiridon" Emergency Clinical Hospital in Iași between 2011 and 2018. Material and methods. A retrospective study on HAI between 2011 and 2018 was initiated at the Oral and Maxillo-Facial Surgery Clinic of the "Sfântul Spiridon" Emergency Clinical Hospital in Iași. Results. Among 21277 surveyed patients the prevalence of patients with at least one HAI was 0,72%. The types of diagnosed HAI were the surgical site infections (54,11%), respiratory infections (15,58 %), device associated infections (14,29%), digestive tract infections (5,63%), urinary tract infections (5,63%), septicemia (2,16%) and cutaneous infections (1,73%).Conclusions. The assessment of the epidemiologic data, risk factors and trends of healthcare-associated infections are necessary for their surveillance, control and prevention.